On the Same Side of the Faultline: Inclusion in the Leader's Subgroup and Employee Performance. (20th February 2015) - Meyer, Bertolt; Shemla, Meir; Li, Jia; Wegge, Jürgen
ABSTRACT Extending theory on faultlines and subgroups, we argue that faultlines splitting a team into homogeneous subgroups can have different effects on team members' individual performance, depending on different intra‐subgroup processes. Specifically, we propose that the effect of faultline strength on individual performance depends on whether a team member's subgroup includes the team leader. Building on the notion of faultline triggers, we further propose that organizational crises exacerbate this interaction because they make social support by the team leader especially important. We tested these assumptions with objective performance data collected over a period of four years from 3263 financial consultants (325 teams) while controlling for the effects of relational demography. Results showed that in teams with strong faultlines, consultants' performance decreased to a lesser extent in crisis years if the consultants shared a subgroup with their team leader. Thus, faultlines had different effects on team members from different subgroups.